Legitimität: Gesellschaftliche, politische und wissenschaftliche Bruchlinien der Rechtfertigung - Graß, Doris; Dammayr, Maria; Rothmüller, Barbara (transcript, 2015)
Whether in finance, care provision or education, current crises affect the stability of models of legitimation, and need to be reconsidered in the context of scientific and political debates. Are forms of legitimation of, say, democracy, service provision, social inequalities and claims to truth or rule becoming fragile? Are new interpretive horizons appearing in discourses of crisis, or are the received, previously unquestioned models of justification perhaps becoming even more convincing? The essays in this anthology investigate the development and course of the fault lines in justification in areas as diverse as politics, finance and labor, education, academia and the media.